Pemeliharaan Ternak Domba di Kebun Kelapa Sawit - Hasan Basri (Jurnal Agripet, 2000)
ABSTRACT.Sheep are small ruminant that have been adapted and close to human. They are easily raised and contribute to family enterprise income. They are usally raised in public land, unplanted paddy field, and under palm plantation. Research on raising sheep under paim plantation was conducted from 9 October 1996 to 21 january 1997. The research was conducted at PT. Pasriwisata, Damar Siput, Rantau Slamat, Eastern Aceh. Thirty sheep were used in this experiment. They were crossbreed of Hairsheep St. Croix males with local female (F1 x F1). Therefore, the sheep had 50 percent of local sheep blood and 50 percent of Hairsheep St. Croix blood. They were borrowed from Sei Putih Liverstock research center, Galang, North Sumatra. They were divided into three group of 6, 10 and 14 heads respectively. Each group was grazing on 1 ha pasture under palm plantation. All sheep got the same treatment and no supplement was fed the animal. They were grazing for 4 hours a day. The result showed that there was no significant differences. ( P 0.05 ) on daily body weight gain among the threatments. Mean daily body weight gain or each group was 30 g, 35 g and 36,22 g for group 6, 10 and 14 heads respectively. This finding was relatively the same as reported by ditjennak ( 1 ) and ginting ( 2 ) where daily body weight gain was about 30 to 40 g for sheep those were extensively grazing under rubber plantation without supplement and were grazing for 6 to 8 hours day. Body weight gain of sheep is not only determined by the excessive availability of forage, but also by the number of sheep that are grazing at the same time on the same pasture. Number of sheep are grazing on the pasture competitively encourages sheep to graze the pasture more. Tilman et al. ( 3 ) stated that animal that eats more give higher body weight gain than animal eats less.